Promotional Effect of Ce-dopant on Al2O3-supported Co Catalysts for Syngas Production via CO2 Reforming of Ethanol - Fayaz, Fahim; Danh, Huong T.; Nguyen-Huy, Chinh; Vu, Khanh B.; Bawadi, Abdullah; Vo, Dai-Viet N. (Elsevier Ltd, 2016)
The effect of ceria promotion on Co/Al2O3 catalysts for ethanol dry reforming has been investigated at stoichiometric feed composition and 973 K under atmospheric pressure. Ce-promoted catalysts were synthesized using a wet co-impregnation method and evaluated in a quartz fixed-bed reactor. X-ray diffraction measurements indicated the formation of CeO2, Co3O4 and CoAl2O4 phases on catalyst surface. Ce-addition eased the reduction process of Co3O4 to CoO phase which was subsequently reduced to metallic Co0 form. H2 and CO yields as well as ethanol conversion increased with growing Ce loading and approached the greatest value at 3wt.%Ce followed by a considerable drop beyond this optimal Ce content. Both promoted and unpromoted catalysts were stable with time-on-stream and the improvement of catalytic performance with Ce-addition was reasonably due to the high oxygen storage capacity of CeO2 promoter which oxidizing carbonaceous species. The heterogeneous nature of deposited carbons containing carbon nanofilament and graphite on spent catalyst surface was evident by scanning electron microscopy. However, the filamentous carbon appeared to be predominant on the surface of spent catalyst in comparison with undesirable graphite responsible for catalyst deterioration. Additionally, Ce-promoted catalysts were resistant to carbon deposition.